2009
DOI: 10.1161/circulationaha.109.859280
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Coronary Angiography by 320-Row Computed Tomography With Lower Radiation Exposure and Maintained Diagnostic Accuracy

Abstract: Background-Noninvasive coronary angiography with the use of multislice computed tomography (CT) scanners is feasible with high sensitivity and negative predictive value; however, the radiation exposure associated with this technique is rather high. We evaluated coronary angiography using whole-heart 320-row CT, which avoids exposure-intensive overscanning and overranging. Methods and Results-A total of 30 consecutive patients with suspected coronary artery disease referred for clinically indicated conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
2
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(199 citation statements)
references
References 50 publications
7
175
2
15
Order By: Relevance
“…4-7 Furthermore, dual-source CT (DSCT), 256-slice, and 320-detector scanner were developed to significantly improve scan times, volume coverage, and spatial resolution. [8][9][10][11][12] With improvement in the technical aspects of coronary computed tomography angiography (CCTA), clinical practice and research are increasingly shifting toward defining the clinical implication of plaque morphology, myocardial perfusion imaging (MPI), and patient outcomes. In this review, we discuss the role of cardiac MDCT beyond coronary angiography, including a comparison with other currently available imaging modalities used to examine atherosclerotic plaque and myocardial perfusion.…”
Section: Ultidetector Computed Tomography (Mdct) Is Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…4-7 Furthermore, dual-source CT (DSCT), 256-slice, and 320-detector scanner were developed to significantly improve scan times, volume coverage, and spatial resolution. [8][9][10][11][12] With improvement in the technical aspects of coronary computed tomography angiography (CCTA), clinical practice and research are increasingly shifting toward defining the clinical implication of plaque morphology, myocardial perfusion imaging (MPI), and patient outcomes. In this review, we discuss the role of cardiac MDCT beyond coronary angiography, including a comparison with other currently available imaging modalities used to examine atherosclerotic plaque and myocardial perfusion.…”
Section: Ultidetector Computed Tomography (Mdct) Is Wellmentioning
confidence: 99%
“…The diagnostic accuracy of 64-slice CCTA Role of Cardiac MDCT of CCTA for exclusion of anatomically significant CAD ( Table 1). [8][9][10][11][12] In a systematic review of the accuracy of DSCT for detection of arterial stenosis in some or all difficult-toimage patients, the pooled, per-patient estimates of sensitivity were 97.7% and 97.7% for patients with arrhythmias and high heart rates, respectively. 15 The corresponding pooled estimates of specificity were 81.7% and 86.3%.…”
Section: Diagnosis Of Cadmentioning
confidence: 99%
“…The image quality tested was limited to patients with a heart rate between 65-75 bpm, and the effect of higher heart rate remains to be studied. The diagnostic accuracy of the second generation 320-detector row CT compared to invasive angiography will need further evaluation but studies from first generation scanner showed highly comparable results (3,7,21).…”
Section: Limitationsmentioning
confidence: 99%
“…Recently it has been shown to be a useful modality to assess patients with low to intermediate risk of suspected acute coronary syndromes presenting to the emergency department (4,5). To minimize radiation exposure, recent advances include the advent use of wide-detector scanners such as the 320 detector row scanner which has a 16 cm cranial-caudal coverage (6) and allows for acquisition of the whole coronary artery tree in one gantry rotation over less than one heartbeat (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…These artifacts can only be eliminated by avoiding the step portion in the ''step-and-shoot'' techniques and can be accomplished by imaging in a single heartbeat as recently suggested using either 320-row coronary CT angiography [11,12] or highpitch prospective spiral acquisition [13,14]. However, the scanners required for these two approaches (320-row CT and fast dual-source 64-row CT) are not as widely available as standard 64-row CT scanners.…”
Section: Cad Coronary Artery Disease Ct Computed Tomography Ecg Electmentioning
confidence: 99%